Innovative Pedagogical Practices Using Technology: The Curriculum Perspective - Nachmias, Rafi; Mioduser, David; Forkosh-Baruch, Alona (International Handbook of Information Technology in Primary and Secondary Education, 2008)
Information and communication technologies (ICT) have affected our lives for over half a century. Yet, the school’s curriculum is still perceived as traditional in its structure and implementation. Attempts to assimilate ICT into schools’ curricula are frequently supported by policymakers. However, significant change in content, teaching and learning processes and assessment methods can actually be detected mainly in focal innovative initiatives within schools. This chapter analyzes case studies of innovative IT-supported pedagogical practices from 28 countries. The analysis refers to conditions required for fostering ICT implementation in the curriculum, with regards to new demands for teaching and learning. This suggests analysis of ICT-related curricular issues in separate subject areas, as well as in integrated subject domains. Further, we discuss desired changes in existing curricula, which may lead to innovative ICT implementation within schools.
Keywords: TICE; numérique